Relationship among four functional classification systems and parent interpredicted intelligence level in children with different clinical types of cerebral palsy. (18th August 2022) - Unes, Sefa; Tuncdemir, Merve; Ozal, Cemil; Cankaya, Ozge; Seyhan Biyik, Kübra; Delioglu, Kıvanc; Gunbey, Ceren; Kerem Gunel, Mintaze; Anlar, Banu
ABSTRACT: Objective: To investigate the relationships between four functional classification systems in children with cerebral palsy (CP) and parent-interpredicted intelligence level, and the functional status in clinical types of CP. Methods: Two hundred and twenty-five children with CP ages between 2 and 18 (mean age 6.5 ± 4.4) years included using the Surveillance of CP in Europe (SCPE) database in Turkey. Gross Motor Function Classification System (GMFCS), Manual Ability Classification System (MACS), Communication Function Classification System (CFCS) and Eating and Drinking Classification System (EDACS) levels were classified by clinical observation, and intelligence quotient (IQ) was determined by parent reports. Results: Correlations were found between all functional levels; the strongest were between GMFCS-MACS (r = 0.784, p < .001), CFCS-EDACS (r = 0.772, p < .001). Strong correlations were found for the IQ-CFCS (r = 0.762, p < .001) and IQ-EDACS (r = 0.634, p < .001). Correlations were stronger in children with bilateral CP and IQ level <70. Conclusions: Taken together, these four classification systems and reported IQ levels can adequately describe overall functioning for children with CP. Our results can guide clinicians in the rehabilitation of children with CP.